A system of didactics activities to develop the sub-skill pronunciation of past tense regular verbs in english language - Solis Corozo, Maite Nicole; Jimenez Cuello, Andrea Karelys (Machala, Utmachala, 2023)
This research was developed with the aim of improving the pronunciation of regular English verbs in the past tense in students of 7th year of basic education parallel ¨A¨ of the school Dr. Camilo Gallegos, located in the Ciudadela Roldos, parish Machala in the school year 2022-2023 through the implementation of a system of activities using audiovisual didactic resources. Although it is well known that technology has advanced by leaps and bounds, however, these technological resources are not fully exploited in the classroom, since they make use of the same traditional education systems (memorisation and repetition) of words and grammatical rules, which does not attract attention or arouse interest in students. Therefore, the intervention proposal of this research was made to encourage future teachers to change that traditional paradigm for a system of modern class activities, implementing technological resources, and managing to capture the maximum attention of students. This research was carried out through a quantitative type of research with an experimental research design, making use of different techniques to obtain the results, such as observation, survey, pre-test for learning diagnosis and finally post-test to verify the results of the didactic activities implemented in class. Finally, the results obtained are shown, indicating the percentage of students who managed to improve their learning and pronunciation.
El presente estudio se realizó con el objetivo de mejorar la pronunciación de los verbos regulares del idioma inglés en tiempo pasado en los estudiantes de 7mo Año de educación básica paralelo ¨A¨ de la escuela Dr. Camilo Gallegos, ubicada en la Ciudadela Roldos, parroquia Machala en el año lectivo 2022-2023 mediante la implementación de un sistema de actividades usando recursos didácticos Audiovisuales. Si bien es conocido, la tecnología ha avanzado a pasos agigantados, sin embargo, estos recursos tecnológicos no son aprovechados completamente en las aulas de clase, puesto que hacen uso de los mismos sistemas de educación tradicionales (memorización y repetición) de palabras y reglas gramaticales lo que no llama la atención ni despierta interés en los estudiantes. Por consiguiente, la propuesta de intervención es esta investigación, fue hecha para incentivar a los futuros docentes, a cambiar aquel paradigma tradicional por un sistema de actividades de clases modernas, implementando recursos tecnológicos, logrando captar la atención máxima de los estudiantes. Esta investigación se llevó a cabo mediante un tipo de investigación cuantitativa con un diseño investigativo experimental, haciendo uso de diferentes técnicas para la obtención de los resultados, tales como observación, encuesta, pre test para el diagnóstico de aprendizaje y finalmente post test para verificar los resultados de las actividades didácticas implementadas en clase. Por último, se muestran los resultados obtenidos, donde se señala el porcentaje de estudiantes que lograron mejorar en su aprendizaje y pronunciación.
Keywords: ACTIVIDAD DIDACTICA; PRONUNCIACION; HERRAMIENTA TECNOLOGICA; APRENDIZAJE